Seismic behavior of RC cantilever beams under low cyclic loading and size effect on shear strength: An experimental characterization. (1st September 2016) - Jin, Liu; Du, Xiuli; Li, Dong; Su, Xiao
Highlights: Seismic shear failure behavior of 8 RC cantilever beams under low cyclic loading are reported. The depth of the RC cantilever beams tested ranges from 200 mm to 1000 mm. The seismic performances of the RC beams with different structural sizes are explored. Under low-cyclic fatigue loads, all the RC beams with stirrups exhibit brittle failure modes. The nominal shear strength of beams follows closely the size effect law proposed by Bažant. Abstract: The main objectives of this study are, on one hand to present an experimental campaign on the seismic shear failure behavior of RC cantilever beams with transverse reinforcement subjected to low-cyclic fatigue loading, and on the other hand to evaluate the possibility of the existence of size effect on the corresponding nominal shear strength of the RC beams. Five groups of geometrically similar RC beams with cross-sectional height ranging from 200 mm to 1000 mm and a shear-span ratio of 2 were designed and tested. Based on the test results, the seismic shear behavior including the failure patterns, the hysteretic characteristics, the bearing capacity, the ductility capacity, the energy dissipation capacity and stiffness degradation are explored. Moreover, the size effect on the nominal shear strength is studied and discussed. The test results and analyses indicate that, (1) the failure patterns of the RC beams having different structural sizes are very similar; (2) under low-cyclic fatigue loadings, even with the transversal reinforcement, the failure of the RC beams is still brittle; (3) with increasing the structural size of the RC beams, the corresponding nominal shear strength, the safety reserve coefficient and the ductility capacity decrease pronouncedly; (4) the test data on the nominal shear strength is in good agreement with Bažant's size effect law.